O‘QITUVCHILARIDA PEDAGOGIK FAOLIYATNI SHAKLLANTIRISHNING O‘ZIGA XOS XUSUSIYATLARI - Tohirova, Sh.M. (SCIENCE and SOCIETY, 2025)
This article discusses the formation of pedagogical activity, which serves not only to develop their pedagogical abilities, but also to increase their general knowledge and skills, and through this process, children learn to manage their own characteristics, which in the future will help them develop as independent and successful people.
Keywords: pedagogy; teacher; skill; education; technique; ability; value; tradition; process; competence